5+6(x-2)=4-8(x-4)

Simple and best practice solution for 5+6(x-2)=4-8(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6(x-2)=4-8(x-4) equation:



5+6(x-2)=4-8(x-4)
We move all terms to the left:
5+6(x-2)-(4-8(x-4))=0
We multiply parentheses
6x-(4-8(x-4))-12+5=0
We calculate terms in parentheses: -(4-8(x-4)), so:
4-8(x-4)
determiningTheFunctionDomain -8(x-4)+4
We multiply parentheses
-8x+32+4
We add all the numbers together, and all the variables
-8x+36
Back to the equation:
-(-8x+36)
We add all the numbers together, and all the variables
6x-(-8x+36)-7=0
We get rid of parentheses
6x+8x-36-7=0
We add all the numbers together, and all the variables
14x-43=0
We move all terms containing x to the left, all other terms to the right
14x=43
x=43/14
x=3+1/14

See similar equations:

| 3x=√2 | | -3+v=-6= | | 36=9-3(x-2 | | -5=4+x= | | 2.6/1.7=n/10.2 | | 8(x+6)+6=-2 | | 2(9x-7)=8 | | 5=x-3/12 | | 1/6=2/5+y | | -7=2-9m | | 36=9-3x-2 | | 11/3+1/4=x | | 0.03x=0.01x+2.9 | | v/v+2+1/v-1=1 | | 2(3x+-3)+x=1 | | -15v-40=1+8v | | 8-2x=14-2x | | 10=2-y+1 | | 3.56x+35.6=71.2 | | 36+2x=-54-3x | | 4x+7x-16=48-5x | | 8x=-2=-9+7x | | 4x+7(x)^2=2 | | 3x−8=7x+4 | | 2(3x+-21)+x=1 | | 77=3.5x | | H(t)=-16^2+50t+30 | | 2x+7=61 | | 5t–4=-2 | | 0=7x^2-112 | | 15t+16=6-5t | | 9x-13x=13 |

Equations solver categories